Sulfasalazine-loaded nanoparticles for efficient inflammatory bowel disease therapy via ROS-scavenging strategy. (January 2023) - Lin, Sen; Zhao, Haosen; Xu, Chang; Zhang, Peng; Mei, Xifan; Jiang, Dingwen
Graphical abstract: Highlights: Sul-MPBs showed sustained and H2 O2 -induced accelerated release of sulfasalazine. Sul-MPBs exhibited ROS-scavenging properties against mitochondrial dysfunction. Sul-MPBs showed remarkable improvement of IBD. Abstract: Inflammatory bowel disease (IBD) is a life-threatening organ dysfunction amplified by complex interactions between genetic, environmental, and immune factors. Sulfasalazine (Sul), an immunosuppressant, can potentially treat autoinflammation-induced disorders; however, clinical application of Sul is hindered by its inability to be directly taken up by cells. To address this challenge, we developed Mn doped prussian blue nanozymes (MPBs) to directly deliver Sul for targeting reactive oxygen species (ROS)-enriched microenvironment. The artificial nanozyme (Sul-MPBs) exhibits reactive oxygen species (ROS)-scavenging properties against hydrogen peroxide (H2 O2 )-mediated mitochondrial dysfunction and possesses both catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx)-like properties in vitro. Furthermore, it significantly enhances therapeutic effects in treating dextran sulfate sodium salt (DSS)-induced IBD via alleviating ROS-mediated inflammatory responses. This study demonstrates good biocompatibility and protective properties of this artificial nanozyme, thus potentially leading to a highly innovative and translational approach to treat IBD efficiently and safely.